Life Repurposed: Finding a New Calling Through Meaningful Occupation - Jennifer Fortuna, PhD, OTR/L (Scholarworks @ WMU, 2021)
Kelly Allen, an occupational therapist and artist based in Grand Rapids, MI, provided the cover art for the Spring 2021 edition of the Open Journal of Occupational Therapy (OJOT). "Follow" is a 16" x 20" painting made from oil on panel. The painting, which features a coati from Central America, is from Kelly's Animal Totem series. After more than 2 decades as a fine artist and educator, she began searching for a career change. Kelly's background in fine art and her desire to help others prepared her for a career in occupational therapy. Certain events in Kelly's life aligned not by chance, but to prepare for her for what was next.